Efficacy of health literacy interventions aimed to improve health gains of higher education students-a systematic review - Jorge Rosário; Beatriz Raposo; Eunice Santos; Sónia Dias; Ana Rita Pedro (BMC, 2024)
Abstract Background Health literacy (HL) among higher education students is low, making them vulnerable about their health. To reverse this trend, higher education institutions promote HL interventions with various topics and methods. A comprehensive understanding of HL interventions is essential to determine whether these interventions meet the health information needs to improve health outcomes (health gains). The aim of this review was to identify and synthesise evidence on the efficacy of HL interventions implemented in academic settings to improve health outcomes. Methods A systematic review was performed followed the PRISMA guidelines, protocol was registered in PROSPERO (CRD42022369869). A search strategy was performed in the EBSCO Host Web platform, the time limit placed was: 01/01/2017 to 30/09/2022. Eligible studies were those published in peer-reviewed journals and involved higher education students over the age of 18 as the subject of the intervention. Eligible interventions included any interventions evaluated in a study with comparison group that included a pre-post measure of health outcomes, were conducted in an academic setting. To methodology quality of included studies, it was used the Joanna Briggs Institute critical appraisal tool. To synthesise results narrative and thematic synthesis was conducted. Results A total of 9 articles were included in this review, identified health literacy interventions with an impact on health outcomes. The total studies involved 2902 higher education students. All 9 studies were randomised controlled trials. The synthesised evidence supports the efficacy of interventions that contributed to positive changes in mental health, attitudes, norms, and self-efficacy of condom use, emotional, social, and psychological well being, subjective sleep quality, sleep latency, and habitual sleep efficiency, physical activity, and self-reported servings fried foods. HL interventions were educational or motivational and related to health promotion, disease prevention or healthcare. Conclusions HL interventions in higher education students can significantly improve health outcomes protecting them from the negative effects of threats for their health. The interventions designed with different strategies are more effective. HL interventions are associated with health benefits on health promotion, disease prevention and healthcare. For the attendance of higher education to be a successful experience, continuity of HL interventions developed in academic settings is necessary.